2022
DOI: 10.1097/md.0000000000029963
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive treatment outcomes of giant cell tumor of the spine: A retrospective study

Abstract: There is no consensus on a treatment strategy for spinal giant cell tumor of bone (GCTB) because of the difficulty in their treatment. Treatment options often include the use of the controversial denosumab, an antibody therapy aimed at tumor shrinkage, different curettage techniques, resection, or a combination of these therapies. The current study aimed to identify treatment methods associated with favorable outcomes in patients with spinal GCTB. We retrospectively reviewed 5 patients with spinal G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…It is worth emphasizing that the histopathological assessment of giant cell tumor of bone (GCTB) following denosumab treatment should be approached cautiously due to the possibility of alterations in cell count and the emergence of new bone [ 24 , 25 , 26 ]. Nevertheless, certain studies have reported no substantial pathological changes upon histopathological analysis following denosumab treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth emphasizing that the histopathological assessment of giant cell tumor of bone (GCTB) following denosumab treatment should be approached cautiously due to the possibility of alterations in cell count and the emergence of new bone [ 24 , 25 , 26 ]. Nevertheless, certain studies have reported no substantial pathological changes upon histopathological analysis following denosumab treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within a multidisciplinary management of spinal tumors, it is important to enhance integration between surgery and other treatments, focusing on timing and proper planning, to reduce the risks and maximize the efficacy of each treatment. Adjuvant therapies, such as chemotherapy for osteosarcoma and Ewing’s sarcoma or Denosumab for giant cell tumor [ 32 ], can facilitate en bloc resection, by reducing the tumor volume and inducing ossification, which makes the lesion margins more identifiable.…”
Section: Discussionmentioning
confidence: 99%